Anti-knock quality of sugar derived levulinic esters and cyclic ethers - Tian, Miao; McCormick, Robert L.; Luecke, Jon; de Jong, Ed; van der Waal, Jan C.; van Klink, Gerard P.M.; Boot, Michael D. (Fuel (Guildford), 2017)
•Anti-knock quality of four sugar-based cyclic ethers and levulinic esters determined.•Experiments carried out on both gasoline engine and constant volume chamber.•Results demonstrate good performance for levulinates and unsaturated cyclic ether.•Anti-knock behavior qualitatively explained with chemical kinetics considerations. The objective of this paper is to investigate the anti-knock quality of sugar-derived levulinic esters (methyl levulinate (ML) and ethyl levulinate (EL)) and cyclic ethers (furfuryl ethyl ether (FEE) and ethyl tetrahydrofurfuryl ether (ETE)). To this end, combustion experiments were carried out in both an engine and a constant volume autoignition device (modified ignition quality tester (IQT)). The results from both apparatuses demonstrate that ML, EL and FEE have superior anti-knock quality to the reference Euro95 gasoline. ETE, conversely, performed markedly worse than the reference fuel on both setups and might therefore be a more appropriate fuel additive for compression ignition engines. The main reason of the distinctions in anti-knock quality can be found in the molecular structure of the neat biofuels. ML and EL are levulinic esters, with a ketone (CO) functionality and an ester (C(O)–O) group on the carbon chain. They can readily produce stable intermediates during the auto-ignition process, thereby slowing down the overall reaction rate. The unsaturated cyclic ether (FEE) has very strong ring C–H bonds. However, the saturated cyclic ether (ETE) has weak ring C–H bonds, which facilitate more readily ring opening reactions. Ethyl side chains on the cyclic ethers further accelerate the reaction rate. Importantly for future research, our results suggest that the modified (IQT) and engine experiments are interchangeable setups with respect to qualitative anti-knock quality evaluation of novel compounds.